EXPERIMENTAL VERIFICATION OF THE EFFICIENCY OF THE ORGANIZATION OF THE NURSING PROCESS IN HEALTH CARE INSTITUTIONS OF LVIV AND LVIV REGION - Bezkorovayna, U. Yu.; Yaremchuk О. V. (Nursing, 2024)
Introduction. Nurses are an essential part of the healthcare system, tasked with addressing both individual and public health issues in changing environmental conditions. They also focus on strengthening health, disease prevention, and providing psychosocial support. The cornerstone of nursing practice is the nursing process, which requires nurses to have both general and professional competencies, practical skills that contribute to enhancing professionalism and competence in practical activities, and creating conditions for further professional growth. The aim of the study – to analyze the ergonomics of nursing staff in healthcare institutions in Lviv city and Lviv region and provide recommendations. The main part. During the study of this problem, in addition to the study of nursing theories and their application in nursing practice, we were interested in aspects of the ergonomics of working time of medical personnel. This is explained by the fact that in the daily work of medical nurses, most of the time is spent on observation, care and performance of functional duties. Medical ergonomics is a branch of professional ergonomics that studies the relationship between people and their working environment in the field of medicine. The main goal of medical ergonomics is to create optimal working conditions for medical personnel in order to increase work efficiency and reduce the risks of occupational diseases and injuries. This discipline examines various aspects of the medical environment, such as the organization of the work space, the arrangement of equipment and tools, the optimization of work processes, and the distribution of responsibilities among members of the medical staff. Medical ergonomics also studies the influence of physical and psychological factors of the working environment on the health and work efficiency of workers in medical institutions. To successfully implement professional competencies, nurses must have soft skills, such as interpersonal communication skills, situational awareness, flexibility and the ability to be diplomatic and tactful. This is due to the fact that they are constantly in contact with patients and their relatives, as well as with work colleagues. Conclusions. Having analyzed the given data, we found that the application of the stages of the nursing process in the healthcare institutions by nurses is not applied to the full extent in practical activities, and the fourth stage is implemented only on the instructions of the doctor, this indicates the full functional dependence of the nurses on the doctor, that does not give nurses the opportunity to independently conduct the nursing process within the limits of nursing competence.